Employment of Sikorsky S61A-4 Nuri helicopters in counter insurgency warfare in Peninsular Malaysia 1968-1989 - Nor Ibrahim Sulaiman; Rohani Ab Ghani (Penerbit Universiti Kebangsaan Malaysia, 2016)
The declaration ending the Malayan Emergency on 30 June 1960 did not mark the end of the Communist Party of Malaya’s (CPM) objective of making Peninsular Malaysia a Democratic Republic of Malaya. In addition to this continued threat, the British withdrew their military forces from Malaysia in 1967, leaving the nation to fend for itself from both internal and external threats. This situation led the government to strengthen its Security Forces (SF) and military assets. One of the air assets acquired was the medium lift helicopters, Sikorsky S61A-4 Nuri. The capabilities of these aircraft in providing air movement of the troops and supplies made the SF dominate over the CTs. The insurrection of the communist insurgency coincided with the introduction of the Nuri in 1968 where its foreseeable roles were demonstrated during the numerous operations launched by the SF in Peninsular Malaysia (1968-1989). This paper aims to highlight the involvement of the Nuri in Op Gubir 11 (a Unilateral Operation), Op Selamat Sawadee (Combined Operation between Malaysia and Thailand), and Op Bamboo with emphasis on Search and Rescue (SAR) operations. It also discussed the threats and challenges faced by the Nuri crew while operating in hostile and challenging environments. The admirable performance of these workhorses was a contributing towards for the eventual signing of the Peace Agreement between Malaysia and the CPM at Hat Yai, Thailand, on 2 December 1989. Also it’s uses the historical approach and most of the references are based on interview with SF’s personnel and the records of Nuri’s ex-pilots.